Characteristics and geological origin of earthquakes and tremor at Katla (S-Iceland) - Sgattoni, Giulia, 1986- (2016)
Katla is a hazardous volcano in south Iceland, in large part covered by the Mýrdalsjökull glacier. It hosts a large caldera with several active geothermal areas and is characterised by persistent seismicity. Katla is one of the most active volcanoes in Iceland with at least 20 phreatomagmatic eruptions in the last 1100 years associated with catastrophic jökulhlaups. The last occurred in 1918. The present repose time is the longest known in history and the 2010 eruption of the neighbouring Eyjafjallajökull volcano prompted scientists’ concerns because the two volcanoes are tectonically connected. The seismic network around Katla was therefore densified. No visible eruption occurred, but in July 2011 a 23 hour tremor burst was associated with a glacial flood which caused damage to infrastructure. This event was accompanied by deepening of the geothermally fed ice cauldrons, increased earthquake activity within the caldera and new seismicity on the south flank. The question arose whether or not a subglacial eruption occurred, i.e. whether the tremor was generated by magmatic processes or by the flood. Analysis of seismic data, including development of new location strategies, and a geological field study of the south flank were conducted to interpret the seismic sources and the volcanological significance of the 2011 unrest. July 2011 marked a change in the seismicity pattern at Katla that suggests a modification of the volcanic system. The tremor burst consisted of two phases originated at the active cauldrons and associated with hydrothermal or magmatic processes and a third phase generated by the flood. The increased seismicity rate inside the caldera and evidence of rapid melting of the glacier may indicate that the tremor was caused by a subglacial eruption. Alternatively, tremor may have been generated by hydrothermal boiling and/or explosions induced by the flood. An increase of heat released by the volcano is required in any case. The seismicity at the southern edge of the glacier in the Gvendarfell area ...